Pengembangan Sistem Informasi Repository Data Akreditasi Institut Teknologi Kalimantan - Aprizal Kamran; Lovinta Happy Atrinawati; Tegar palyus fiqar (Jurnal Komputer Terapan, 2020)
Accreditation is an assessment activity based on predetermined standards and requirements to guarantee the quality and performance of education for every university in Indonesia. The Study Program Accreditation Instrument version 4.0 is needed to compile performance into reports. The nstrument is the Study Program Performance Report. Institut Teknologi Kalimantan (ITK), as one of the institutions, ITK preparing the Study Program Performance Report with manual method so that during the preparation of the report, there was duplication of accreditation data. Because thedata is made from more than one source, collecting accreditation data is still using email. This causes data not stored, and it is not easy to find historical data every year. Therefore, this research was conducted to develop an accreditation management information system, especially Study Program Performance Report, so that accreditation data can be archived and managed by each Study Program at ITK. This system also makes it easier for the Pusat Jaminan Mutu to monitor the performance. The software development method used in this research is the Agile methodology with ScrumMethod. The development uses the Laravel framework, which has implemented a Model, View, Controller architecture. This research resulted in an information system accreditation for the Study Program Performance Report.